1975
DOI: 10.1111/j.1432-1033.1975.tb02210.x
|View full text |Cite
|
Sign up to set email alerts
|

Flavocytochrome b2: Simulation Studies of the Electron‐Transfer Reactions among the Prosthetic Groups

Abstract: Simulation studies by digital computer were undertaken in order to test and clarify the interpretations deduced from experimental data concerning the electron transfer mechanism from I<-lactate to flavocytochrome h,, which were presented in a preceding paper in this journal.The reaction scheme proposed as the "best" one is composed of 7 steps. It allows the best fitting of the time courses established for the oxidized flavin (Flax), the flavin semiquinone (Flsq), the fully reduced flavin (Fired), and the reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

1975
1975
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 7 publications
(3 reference statements)
3
32
0
Order By: Relevance
“…As the rate of phase I1 is changed neither by decreasing 50-fold L-lactate concentration nor varying the enzyme concentration in a large range, the second interpretation is the only possible one. The possibility that the slower limiting step in phase I1 should correspond to the flavin disproportionation reaction is excluded by the relatively high rate of this process (80 s-') as required for the correct simulation studies to be reported later [50].…”
Section: The Entry Of the Third Electron Is Very Slowmentioning
confidence: 99%
See 1 more Smart Citation
“…As the rate of phase I1 is changed neither by decreasing 50-fold L-lactate concentration nor varying the enzyme concentration in a large range, the second interpretation is the only possible one. The possibility that the slower limiting step in phase I1 should correspond to the flavin disproportionation reaction is excluded by the relatively high rate of this process (80 s-') as required for the correct simulation studies to be reported later [50].…”
Section: The Entry Of the Third Electron Is Very Slowmentioning
confidence: 99%
“…7. A detailed critical presentation of the simulation will be given in a following paper [50]. The kinetic arguments taken into consideration are standard ones in the theory of multi step sequential reversible processes (see reaction scheme) [55].…”
Section: Comments On The"simp1est" Reaction Scheme Proposedmentioning
confidence: 99%
“…It has been shown that in the tetramer there are privileged heme-flavin pairs, between which electron transfer is rapid [22, Electron transfer between any member of one pair to any member of another pair is supposed to be slow, with rates lower than 10 s-' [23]. The rate constant for lactate to flavin transfer, which is the slow step in the forward reaction, was estimated by simulation studies to be 120 s-' at 24 "C [20,22]. Furthermore, the measured k,,, for the reverse reaction found in this work is 3.6 s -I ; this low rate cannot be due to slow bromolactate dissociation, for the following reason.…”
Section: Oxidation State Of the Heme During Turnovermentioning
confidence: 99%
“…New kinetic schemes capable of explaining data obtained with deuterated lactate are proposed. These new schemes differ from that of Capeillere-Blandin in that : (a) the hypothesis of simultaneous prosthetic group reduction for the two protomers of one given dimer is abandoned; (b) the limiting step of the slow phases of heme and flavin reduction is a slow interprotomer electron exchange between a heme pair, a flavin pair or heme and flavin; (c) a rather fast conformational change controlled by the redox state of heme or flavin of one protomer can modulate the rate of electron transfer in another protomer.These new kinetic schemes allow us to determine the rate of intraprotomer and interprotomer electron transfer and to decide precisely how these steps are modified by the proteolytic cleavage of 'intact' enzyme to 'cleaved' enzyme.The mechanism of electron transfers in flavocytochrome h2 was reinvestigated by Capeillere-Blandin et al [1,2] who proposed a 'minimum' mechanism capable of explaining with sufficient accuracy all data available at the time. The proposed mechanism includes three kinds of electron transfer: substrate, i.e.…”
mentioning
confidence: 99%
“…The mechanism of electron transfers in flavocytochrome h2 was reinvestigated by Capeillere-Blandin et al [1,2] who proposed a 'minimum' mechanism capable of explaining with sufficient accuracy all data available at the time. The proposed mechanism includes three kinds of electron transfer: substrate, i.e.…”
mentioning
confidence: 99%